High and fast carbon dioxide capture of hydroxypyridine-based ionogel depending on pore structure of mesoporous silica vesicle in the simulated flue gas. (May 2019) - Xue, Chunfeng; Feng, Lin; Zhang, Qian; Huang, Ruichao; Hao, Yanan; Ma, Xuli; Liu, Gang; Li, Kaixi; Hao, Xiaogang
Graphical abstract: Different pore diameter of the substrate imposes decisive effect on the IL dispersion style and final CO2 diffusion and adsorption rate. Highlights: Mesoporous silica vesicle with three kinds of pore structure is prepared for loading ionic liquid. Ionogel MSV100-10 shows CO2 adsorption capacity of 1.69 mmol/g at 50 °C and partial pressure of 0.2. The large mesopore allows the formation of IL pairs and keeps necessary pathway for CO2 diffusion. The ionogel MSV100-10 well performs capacity retention of 95% after 10 sorption cycles. Abstract: Multiple active sites containing ionic liquid (IL) tetrabutylphosphonium 2-hydroxypyridine ([P4444 ][2-Op]) is prepared and loaded into mesoporous silica vesicle (MSV) with three kinds of pore structure for fabricating ionogels to capture CO2 from simulated flue gas (CO2 /N2 ). The ionogel MSV100-10 achieves CO2 adsorption capacity of 1.69 mmol·(g-ionogel) –1 (that is 11.77 mmol·(g-IL) –1 ) in less than 10.0 min at 50 °C and CO2 partial pressure of 0.2. The high adsorption capacity and rate can be ascribed to its large pore size and pore volume, which offer not only enough nanospace for highly dispersed IL but also necessary pathway for fast diffusion of guest molecule CO2 . Small mesopores of the supports benefit to form monomolecular layers for the lowly loaded IL due to their strong nano-confinement effect but are easily blocked by highly loaded IL. The support with large vesicle-like pores allow the formation of IL pairs for the lowly loaded IL due to their weak nano-confinement effect and keep necessary pathway for CO2 diffusion in the highly loaded ionogel. The ionogel MSV100-10 performs capacity retention of 95% after 10 sorption cycles. The ionogel MSV100-10 featuring with low loading and cost, rapid adsorption, high capacity and excellent cyclic stability make it a competitive candidate in CO2 capture from flue gas.